1993
DOI: 10.1093/cercor/3.6.515
|View full text |Cite
|
Sign up to set email alerts
|

Information Cascade from Primary Auditory Cortex to the Amygdala: Corticocortical and Corticoamygdaloid Projections of Temporal Cortex in the Rat

Abstract: Corticocortical and corticoamygdaloid connections of temporal cortext and perirhinal cortex (PRh) were examined in the rat with the anterograde tracer Phaseolus vulgaris leucoagglutinin (PHA-L). Iontophoretic injections of PHA-L into area TE1 resulted in columnar axonal terminations in surrounding and contralateral regions of temporal neocortex and in the striatum, but not in the amygdala. Within temporal neocortex, labeled fibers were present locally in adjacent regions of TE1, as well as in TE2d, TE1v, TE3v,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
239
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(264 citation statements)
references
References 47 publications
24
239
1
Order By: Relevance
“…The middle temporal gyrus can inhibit the function of the amygdala, facilitate the extinction of fear conditioning [52,53] , and is linked to episodic memory as well as language processing [54] . Lower…”
Section: Discussionmentioning
confidence: 99%
“…The middle temporal gyrus can inhibit the function of the amygdala, facilitate the extinction of fear conditioning [52,53] , and is linked to episodic memory as well as language processing [54] . Lower…”
Section: Discussionmentioning
confidence: 99%
“…The fact that zif268 staining in this layer is unchanged in rats retrieving appetitive remote memories suggests that this pathway is not engaged as a result of tones with appetitive-related features. Sensory information about appetitive CSs may reach the Te2 cortex via layers II/III, which is connected to the Te1 auditory cortex (Romanski and LeDoux 1993a) and which also receives some sparse afferents from subcortical nuclei. In addition, a recent study showed that thalamic inputs to the cortex terminate also in the layer V/VI (Constantinople and Bruno 2013), two of the layers in which we found enhanced activity after memory retrieval.…”
Section: Layer IVmentioning
confidence: 99%
“…The major corticofugal projections are glutaminergic (Paxinos 2004). Unlike the primary auditory cortex Te1, the Te2 sends axons to the lateral amygdala (Romanski and LeDoux 1993a;Shi and Cassell 1997), a key site for fear memory. In vitro studies have shown that descending axons from the auditory cortex to the lateral amygdala display long-term potentiation (LTP) (Bissière et al 2003;Fourcaudot et al 21 2009).…”
Section: Layer Vmentioning
confidence: 99%
“…A large lesion of the AC does not prevent the acquisition of conditioned behavioral responses (28,38,39). These findings indicate that the cortical BF shift is not directly involved in evoking conditioned behavioral responses.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it has been concluded that the AC is not necessary for but can mediate simple fear conditionings (38). The neuronal circuit in adult animals for auditory signal processing is plastic (44).…”
Section: Physiological Auditory Memory Trace Vs Physiological Associmentioning
confidence: 99%